2003
DOI: 10.1083/jcb.200303036
|View full text |Cite
|
Sign up to set email alerts
|

Defining desmosomal plakophilin-3 interactions

Abstract: Plakophilin 3 (PKP3) is a recently described armadillo protein of the desmosomal plaque, which is synthesized in simple and stratified epithelia. We investigated the localization pattern of endogenous and exogenous PKP3 and fragments thereof. The desmosomal binding properties of PKP3 were determined using yeast two-hybrid, coimmunoprecipitation and colocalization experiments. To this end, novel mouse anti-PKP3 mAbs were generated. We found that PKP3 binds all three desmogleins, desmocollin (Dsc) 3a and -3b, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
143
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(156 citation statements)
references
References 49 publications
11
143
0
Order By: Relevance
“…Plakophilins share a small region of conserved amino acid identity in the amino terminus termed the HR2 domain (Bonne et al 2003). The function of this domain is currently unclear ( Figure 5A); however, previous studies have suggested this domain in plakophilin-1 plays a role in mediating interactions with desmoplakin (Sobolik-Delmaire et al 2006).…”
Section: Mutations Near the Hr2 Domain Disrupt Interactions With Desmmentioning
confidence: 99%
See 1 more Smart Citation
“…Plakophilins share a small region of conserved amino acid identity in the amino terminus termed the HR2 domain (Bonne et al 2003). The function of this domain is currently unclear ( Figure 5A); however, previous studies have suggested this domain in plakophilin-1 plays a role in mediating interactions with desmoplakin (Sobolik-Delmaire et al 2006).…”
Section: Mutations Near the Hr2 Domain Disrupt Interactions With Desmmentioning
confidence: 99%
“…Structurally, plakophilins are comprised of 9 armadillo repeats located in the carboxyl and amino termini that are largely unrelated to one another (Choi and Weis 2005). In addition, there is a relatively small amino acid sequence in the extreme amino terminus, termed the HR2 domain that is highly conserved among plakophilins and is not present in p120 (Bonne et al 2003). The functional significance of the HR2 domain is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this model, PKP1 is highly expressed in the suprabasal layers of the epidermis where desmosomes are larger and more numerous than in the lower layers of the tissue. In contrast, PKP3 overexpression does not result in larger desmosomes or an increase in desmosome number (Bonne et al 1999;Schmidt et al 1999;Bonne et al 2003). However, PKP3 interacts with the largest number of desmosomal proteins, including desmoplakin, plakoglobin, all three desmoglein proteins, Dsc 3a and 3b, and Dsc 1a and 2a (Hatzfeld 2007).…”
Section: Plakophilinsmentioning
confidence: 99%
“…25 Moreover, PKP1, for which strong in vitro association with the 'a' form of Dsc1 has been reported, 24 was also found to overlap with the 'b' form. 26 The possibility that Dscb isoforms contain a PKP-binding domain should be investigated further.…”
Section: Dsc2 A897kfsx4 Polymorphism In Arvc Probands M De Bortoli Et Almentioning
confidence: 99%